SOCIAL NETWORK’S FUNCTIONAL USAGE BY THE CHINESE CYBERNATIONALISTIC MOVEMENT - Lian, Deng; Frutos, Sonia (Revista Inclusiones, 2019)
As the process of China’s industrialization and the penetration of Internet continue, the Chinese Cybernationalistic Movement (CCM) has become a notable and significant phenomenon. In this study the function of the social networks during the cybernationalism movement will be examined through Big Data and Natural Language Processing (NLP) technologies. Two case studies of more than 3000 examples will be conducted, both of them are highly connected with the recent incident. Not only the contribution of the social network to the self-identification, the choice of the adversary, and the movement core values of the CCM will be presented through their analysis, but also the action frames of the CCM can be confirmed.